Adaptive twisting sliding mode algorithm for hypersonic reentry vehicle attitude control based on finite-time observer. (June 2018) - Guo, Zongyi; Chang, Jing; Guo, Jianguo; Zhou, Jun
Abstract: This paper focuses on the adaptive twisting sliding mode control for the Hypersonic Reentry Vehicles (HRVs) attitude tracking issue. The HRV attitude tracking model is transformed into the error dynamics in matched structure, whereas an unmeasurable state is redefined by lumping the existing unmatched disturbance with the angular rate. Hence, an adaptive finite-time observer is used to estimate the unknown state. Then, an adaptive twisting algorithm is proposed for systems subject to disturbances with unknown bounds. The stability of the proposed observer-based adaptive twisting approach is guaranteed, and the case of noisy measurement is analyzed. Also, the developed control law avoids the aggressive chattering phenomenon of the existing adaptive twisting approaches because the adaptive gains decrease close to the disturbance once the trajectories reach the sliding surface. Finally, numerical simulations on the attitude control of the HRV are conducted to verify the effectiveness and benefit of the proposed approach. Highlights: A finite-time observer-based adaptive controller is proposed to deal with the unknown disturbances. A novel adaptive twsiting algorithm with chattering attenuation is exploited for attitude tracking control problem of hypersonic reentry vehicle. The stability proof of the algorithm is given by using Lyapunov method and the finite time convergence is provided in spite of biased measurements. The attitude command can be tracked in finite time by using the proposed method in spite of biased measurements.